2020
DOI: 10.1177/1077801220923748
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Wellness and Recovery of Young Women Experiencing Gender-Based Violence and Homelessness: The Role of Trauma-Informed Health Promotion Interventions

Abstract: Little is known regarding the types of interventions most effective in supporting wellness and recovery of victims of gender-based violence, particularly those simultaneously experiencing homelessness. This qualitative study explored the experiences of 18 young women experiencing gender-based violence and homelessness who participated in a community-based, trauma-informed group intervention in Toronto, Canada. Participants completed audio-recorded and transcribed semi-structured interviews, analyzed using them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…The study, part of a realist informed longitudinal evaluation of a community-based 16-week psychoeducation group intervention, identified improvements in quality of life, capturing physical, psychological health, social relationships, and the overall environment, and reductions in experiences of victimization among female identified youth experiencing GBV and homelessness 12 months following enrolment, with no significant changes in other health and well-being outcomes. Prior qualitative research by our team revealed that participants valued the safe, women-only space, the shared lived experiences, and tailored psychoeducation, suggesting the intervention is acceptable to service users (29). Furthermore, our findings of improved quality of life and reduced experiences of victimization are supported by prior qualitative findings by our team, highlighting perceived improvements in self-confidence, coping, health, interpersonal relationships, and future directedness as a result of program participation (29).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The study, part of a realist informed longitudinal evaluation of a community-based 16-week psychoeducation group intervention, identified improvements in quality of life, capturing physical, psychological health, social relationships, and the overall environment, and reductions in experiences of victimization among female identified youth experiencing GBV and homelessness 12 months following enrolment, with no significant changes in other health and well-being outcomes. Prior qualitative research by our team revealed that participants valued the safe, women-only space, the shared lived experiences, and tailored psychoeducation, suggesting the intervention is acceptable to service users (29). Furthermore, our findings of improved quality of life and reduced experiences of victimization are supported by prior qualitative findings by our team, highlighting perceived improvements in self-confidence, coping, health, interpersonal relationships, and future directedness as a result of program participation (29).…”
Section: Discussionsupporting
confidence: 73%
“…Prior qualitative research by our team revealed that participants valued the safe, women-only space, the shared lived experiences, and tailored psychoeducation, suggesting the intervention is acceptable to service users (29). Furthermore, our findings of improved quality of life and reduced experiences of victimization are supported by prior qualitative findings by our team, highlighting perceived improvements in self-confidence, coping, health, interpersonal relationships, and future directedness as a result of program participation (29).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Because recovery of women survivors of IPV is a substantial focus of social care and trauma work practice and policy (e.g., community-based, trauma-informed group interventions) (Allen & Wozniak, 2010;Reid et al, 2020) and forgiveness has been found as one important element in their recovery (Flasch et al, 2017;Yick, 2008), in-depth understanding of forgiveness could contribute more to the practice and policy on their personal healing and recovery. Thus, the present study reported herein was thus to explore the forgiveness process of women survivors of IPV who have left an abusive relationship, including perceived changes (e.g., specific changes in different periods after separation) and the way in which they underwent them.…”
Section: The Present Studymentioning
confidence: 99%
“…Specifically, in relation to sexual health, the importance of sexual health improvement and prevention activities are recommended [ 7 , 8 ]. From a sexual health perspective, there has been increased attention on issues including sexual transmitted infections (STIs) [ 9 ], HIV and AIDS [ 10 ], youth pregnancy [ 11 ], contraception [ 12 ] and gender-based violence [ 13 ]. For children and young people, relationship and sexuality education (RSE) programmes have been developed to address these concerns for the purpose of providing knowledge and information to ultimately lead to a satisfying and fulfilling adult life [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%